1994
DOI: 10.1093/oxfordjournals.humrep.a138509
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial thickness: a predictor of implantation in ovum recipients?

Abstract: In a retrospective study, the relationship between endometrial thickness and pregnancy rate has been studied in 59 ovum recipient women. Transvaginal ultrasound assessment of endometrial thickness was performed immediately prior to ovum transfer: 19 pregnant recipients had a mean endometrial thickness of 10.24 mm +/- 2.63 SD, 40 nonpregnant recipients had an endometrial thickness of 8.62 mm +/- 3.49 SD (t = 1.805, P = 0.0382). Only two pregnancies occurred in 15 recipients with an endometrial thickness < 7.5 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
89
0
3

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(97 citation statements)
references
References 0 publications
4
89
0
3
Order By: Relevance
“…The previous reports evaluating the association between endometrial thickness and pregnancy outcome in oocyte donation cycles used either cleavage stage embryo transfer or a mixture of cleavage and blastocyst stage transfer; therefore, they did not maximally control the embryo factor. [5,7,12,[28][29][30]. Clearly our results should be interpreted with caution due to our small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…The previous reports evaluating the association between endometrial thickness and pregnancy outcome in oocyte donation cycles used either cleavage stage embryo transfer or a mixture of cleavage and blastocyst stage transfer; therefore, they did not maximally control the embryo factor. [5,7,12,[28][29][30]. Clearly our results should be interpreted with caution due to our small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…Women with thin endometria have lower pregnancy rates, largely related to implantation failure 1, 2, 3, 4, 5, 6. The authors recently found high blood impedance in the uterine radial artery in patients with a thin endometrium4 and that vitamin E, L‐arginine, and sildenafil citrate treatments, which increase the blood flow of the uterine radial artery, helped to thicken the endometrium 7.…”
Section: Introductionmentioning
confidence: 99%
“…The endometrial proliferation can sometimes even be less than the ideal thickness (3). It therefore prevents endometrial development and can cause a problem regarding implantation in some cases.…”
Section: Introductionmentioning
confidence: 99%